Music and Visual Art Training Modulate Brain Activity in Older Adults - Alain, Claude; Moussard, Aline; Singer, Julia; Lee, Yunjo; Bidelman, Gavin M.; Moreno, Sylvain (Frontiers in Neuroscience, 2019)
Cognitive decline is an unavoidable aspect of aging that impacts important behavioral and cognitive skills. Training programs can mitigate age-related cognitive decline, yet precise characterization of the psychological and neural underpinnings supporting different training programs is lacking. Here, we assessed the short-term effect and long-term maintenance (3-month follow-up) of 3-month music and visual art training programs on neuroelectric brain activity in older adults using a partially-randomized intervention design. During the pre-, post- and follow-up test sessions, participants completed a brief neuropsychological assessment. High-density EEG was measured while participants were presented with auditory oddball paradigms (piano tones, vowels) and during a visual GoNoGo task. Neither training program significantly impacted neuropsychological measures, compared to a non-active control group. However, participants enrolled in the music and visual art training programs showed enhancement of auditory evoked responses to piano tones that persisted for up to three months after the training ended, suggesting robust and long-lasting neuroplastic effects. Both music and visual art training also modulated visual processing during the GoNoGo task, although these training effects were relatively short-lived and disappeared three months after the training ended. Notably, participants enrolled in the visual art training showed greater changes in N1 distribution than those from the music or control group. Conversely, those enrolled in music showed greater response associated with inhibitory control over the right frontal scalp areas than those in the visual art group. Our findings reveal a causal relationship between art training (music and visual art) and neuroplastic changes in sensory systems, with some of the neuroplastic changes being specific to the training regimen.